Supply Chain And Outsourcing Practices In The Food Processing Industry - Al-Shahri, Ahmed Ali (2008)

(untitled)
The Malaysian food processing industry has been experiencing a major transformation, driven by the emergence of large retail chains and the changing consumption patterns and lifestyles. However, no empirical studies have been conducted to investigate the attempts undertaken by companies in the industry in taking advantage of supply chain management and outsourcing applications. Moreover, a critical review of outsourcing models from literature showed that the majority of the models developed were ambiguous, assumed outsourcing is only limited to non-core functions and lack a clear-cut decision making methodology. Also, none of the examined models was developed specifically for the food processing industry. Therefore, this research aims to provide a detailed analysis of the outsourcing and the supply chain activities in the Malaysian Food processing industry and develop a model for outsourcing decision making in the food processing industry that will allow companies to decide their outsourcing policy for any intended outsourcing project. Data for this research were collected through literature review, expert interviews, and survey questionnaire. The survey questionnaire was used to gather empirical data on outsourcing and supply chain management issues in the Malaysian food processing industry. Five hundred questionnaires were mailed to randomly chosen companies in a 5-month period that yielded a response rate of 11%. The outsourcing decision making model was developed using the Analytical Hierarchical Process (AHP), and validated by conducting structured interviews with 25 purchasing managers from different food processing companies and analyzed using the Expert Choice Software (v. 9.5). The results indicated that modern SCM principles have not penetrated well into the Malaysian food processing sector. Only 44% of the respondents have strategic partnership(s), and 39% indicated an increase in strategic partnerships(s) in the last three years. Companies outsource both core and non-core function. The top five outsourced functions were packaging (60.4%), import/export management (58.3%), transportation management (58.3%), processing (56.3%), and warehousing (54.2%). Main reasons influenced the respondents to resort to outsourcing included suppliers’ compatibility (83%), lack of in-house capability (73%), and complexity of function (56%). Lack of advanced communication systems and competition scored the highest as the most obstacles faced in SC execution with 3.39 and 3.32 respectively. The outsourcing model output indicated that those companies that outsource to solve short-term problems tend to adopt a short-term outsourcing policy which does not emphasize on relationship. On the contrary, companies that tend to outsource to transform their businesses through significant improvements tend to outsource strategically in which strategic partnership must be sought. Otherwise, investing and performing internally is the best alternative. The contribution of this research is that it has presented empirical evidence on the practices of outsourcing and SCM in the Malaysian food processing industry. Moreover, an outsourcing model was developed to assist food processing companies in identifying their outsourcing policies in accordance with the objectives of the outsourcing project.